2009
DOI: 10.1007/bf03326128
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of phototrophic bacteria in treating pharmaceutical wastewater

Abstract: AB STRACT: A suspended growth photobioreactor was utilized to treat pharmaceutical wastewater by a wild strain purple non-sulfur photosynthetic bacterium isolated from the soil. The strain was named Z08 and identified as Rhodobacter-sphaeroides by 16SrDN. The photobioreactor was illuminated externally with two (40 W) fluorescent compact light sources on both sides. Its operation pH and temperature were between 6.8 -7.0 and 20 -30 ºC, respectively. Optimum growth of the isolate was obtained after enrichment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…Public awareness were raised after a study sh owed that organic wastewater contaminants, including PPCPs, were present in 80 % of 139 U.S. streams (Kolpin et al, 2002). Although the concentration levels of PPCPs found in the environment are at trace concentrations, their chemical persistence, microbial resistance and synergistic effects are still unknown (Ankley et al, 2007;Madukasi et al, 2010), which is a cause for concern. Moreover, low concentrations can elicit adverse effects on aquatic life (Miege et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…Public awareness were raised after a study sh owed that organic wastewater contaminants, including PPCPs, were present in 80 % of 139 U.S. streams (Kolpin et al, 2002). Although the concentration levels of PPCPs found in the environment are at trace concentrations, their chemical persistence, microbial resistance and synergistic effects are still unknown (Ankley et al, 2007;Madukasi et al, 2010), which is a cause for concern. Moreover, low concentrations can elicit adverse effects on aquatic life (Miege et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…adjustment, oxidation, sand filtration (Saleem 2007), ozone use, Fenton's method, coagulation/flocculation, electrocoagulation (Dixit and Parmar 2013), photelectrocoagulation, peroxi-electrocoagulation, peroxi-photelectrocoagulation, sedimentation, membrane separation, UV irradiation, adsorption, chlorination, distillation, solar photo-Fenton, reverse osmosis, bacterial treatments (Madukasi et al 2010), fungal treatment (Spina et al 2012), algal treatment, phytoremediation and methods using membrane bioreactor (MBR) (Chang et al 2008), anaerobic fixed film reactor (AFFR) (Rao et al 2004), aerobic sequencing batch reactor (ASBR) (Patil et al 2013), membrane-aerated biofilm reactor (MABFR) (Wei et al 2012) and activated sludge (Mayabhate et al 1988). Vanerkar et al (2013) studied the physicochemical treatment of herbal PIWW.…”
Section: Treatment Methods Used In Pharma Industriesmentioning
confidence: 99%
“…They collected the samples from nine different points situated in the industry and observed the range of sulphates 44-1,527 mg/l, TDS 484-1,452 mg/l, total suspended solids 24-84 mg/l and COD 1,257.9-1,542.9 mg/l. Madukasi et al (2010) characterized the pharmaceutical wastewater and observed the concentration in mg/l for total suspended solids 425 ± 2.3, total dissolved solids 1,600 ± 1.1, total nitrogen 533.7, BOD 146.7 ± 0.3, Zn 0.056, iron 2.1, Mn 0.605, Cu 0.022, acetic acid 422.7, propionic acid 201.3 and butyric acid 304.5. A suspended growth photobioreactor employing the wild strain of purple nonsulphur photosynthetic bacterium Rhodobacter sphaeroides was utilized to treat the wastewater.…”
Section: Characteristics Of Pharmaceutical Industries' Wastewatermentioning
confidence: 99%
See 2 more Smart Citations